Docetaxel-Loaded Solid Lipid Nanoparticles Suppress Breast Cancer Cells Growth with Reduced Myelosuppression Toxicity [Erratum] - Yuan Q (Dove Medical Press, 2020)
Yuan Q, Han J, Cong W, et al. Int J Nanomed. 2014;9(1):4829– 4846.The authors of this article have advised that there is an error in Figure 2A of this published paper. The representative photo of flow cytometry profile of 10 nM DSN treated cells is the same as 1 nM DSN treated cells. This is incorrect and this error was introduced during the editing process by Dovepress.Read the original article